Faktor-Faktor Yang Berhubungan Dengan Kejadian Preeklamsia Pada Ibu Hamil Di Kabupaten Kediri Jawa Timur - Katmini Katmini; Febrina Dwi N; Astri Yunita (Poltekkes Kemenkes Surakarta, 2018)
Background: The high MMR in 2015 is a big problem in Indonesia, which is 305 per 100,000 live births (Profile of Indonesian Population Results Supas, 2015). The Indonesian Demographic and Health Survey (2012) shows that MMR in Indonesia is still high at 359 per 100,000 KH. This rate is slightly decreased when compared to IDHS (1991) which is equal to 390 per 100,000 KH. The third goal of the Sustainable Development Goals is good health (Ministry of Health 2015), reducing MMR to 102 per 100,000 KH. Maternal mortality in 2010-2012 was caused by an enhancement in the incidence of preeclampsia, eclampsia and other factors, such as social problems, culture, lack of education, and economic problems. Method: The study was conducted at the Public Health assisted by Kediri Regency in April 2018. It used Quantitative research method by an Explanatory Study with the design of Case Control Study. The number of samples was 100 pregnant women from the Public Health in Kediri Regency. The independent variables were the age of pregnant women, education, employment, Body Mass Index and weight. The dependent variable was preeclampsia. The Primary data was conducted by interview using questionnaires and was supported by secondary data. And the data was analyzed by Bivariate Analysis with Chi Square using SPSS 22. Results. From the results of bivariate analysis using the chi square test, there was a relationship between the age of pregnant women (OR = 0.35; 95% CI = 0.15 to 0.80; p = 0.012), parity (OR = 0.26; 95% CI = 0.11 to 0.62; p = 0.002), education level (OR = 0.15; 95% CI = 0.06 to 0.38; p = <0.001) and employment (OR = 8.66; 95% CI = 3.46 to 21.65; p = <0.001) with preeclampsia. There was no correlation between BMI (OR = 1.06; 95% CI = 0.47 to 2.38; p = 0.870), BB (OR = 0.93; 95% CI = 0.41 to 2.09; p = 0.869), with preeclampsia. Conclusion. There is a correlation between the age of pregnant women, parity, education level and occupation with preeclampsia. Other variables which are not related to the case of preeclampsia are Body Mass Index and weight.